The Santanderean Creole Goat: Genetic Heritage and Productive Sustainability in Northeastern Colombia - Cala Moreno, Nelson; Caicedo Blanco, Yuly Andrea; García Arévalo, Jorge Leonardo; Toledo Alvarado, Hugo Oswaldo (Spei Domus, 2025)
The Santanderean Creole Goat represents a valuable zoogenetic resource adapted to the semi-arid conditions of the Chicamocha Canyon in Colombia. This outreach article examines its productive traits, health challenges---particularly gastrointestinal parasitism caused by nematodes---and sustainable management strategies. Through a comprehensive approach that integrates genetic, nutritional, animal welfare, and health management aspects, the potential of this creole breed is highlighted as a productive alternative for small rural farmers and its importance in regional food security.
Keywords: Santanderean Creole Goat; native breed; gastrointestinal nematodes; sustainability; goat production